Application of thermosonication treatment in processing and production of high quality and safe-to-drink fruit juices - Abdullah, Norazlin; Chin, Nyuk Ling (Elsevier, 2014)
The demand for higher quality and freshness in fruit juices with absence of additives and preservatives has encouraged the use of ultrasound technology in juice processing. Thermosonication is a novel and good alternative technique to replace the conventional heat treatment process. It has potential in enhancing quality and safety of the fruit juices. It is more energy-efficient than conventional thermal technology. It is also more efficient, safe and reliable than ultrasound application alone by itself to achieve the limit of food-borne pathogens destruction. This review covers the effects of ultrasound-heat combined application on fruit juices quality and safety aspects.